(untitled) (The Harvest, 2024)
Rishi, Devata, Chanda, are the three foundational pillars of the four Vedas: Rik,Yaju, Sama and Atharva. Each of these four is collection of mantra and mantra collection is called Samhita. Each Samhita consists of Brahmana, Aranyaka and Upanisad texts and these are interpretive texts of Samhita. Both Samhita and interpretive texts form the vast body of Vedic literature. Samhitas are original texts whereas Brahmana and Aranyaka are their interpretations, and the Upanisads are philosophic texts of the Vedas. Rishi, Devata and Chanda are formative elements of the Vedas. Rishis are the wise scholars who have realized Vedic mantras and handed the same to their disciples which in the long run develop different Sakha or branches of each Veda and such sakha altogether were 1131 and now only 26 sakha with their texts are available. Concept of Devata is suggestive of the theme and the subject matter of Vedic literature. In the Vedas Devatas are representatives of divine entity having certain physical form. The sun, the wind/ Indra and Agni (fire) are three Devata of the space, interspace and the earth. Vedas discusses One Almighty Brahma/ Purusha taking different forms as Devata based on various performances. Each Vedic Samhita and all interpretive literature follow structural pattern and especially Rigveda follows rigid metrical pattern. Each mantra of Vedic literature demands proper understanding of its Rishi, Devata and Chanda in order to capture its true spirit.